1994
DOI: 10.1159/000106686
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Differences in β/A4 Protein Subtypes in the Parahippocampal Gyrus and Frontal Cortex in Alzheimer's Disease

Abstract: The density of diffuse, primitive and classic β/A4 protein deposits was estimated in sulci and gyri in the frontal cortex and parahippocampal gyrus (PHG) in 8 cases of Alzheimer''s disease. Total β/A4 deposit density was similar in the frontal cortex and PHG but the ratio of primitive and classic deposits to the total was greater in the PHG compared with the frontal cortex. Total β/A4 deposit density was greater in the depths of the sulci, but the proportions of the various β/A4 subtypes were similar in sulci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Both Aß plaques and neurofibrillary tangles were found concentrated in sulcal fundi compared with gyral crowns. This confirms previous observations on the distribution of plaques made by several groups including our own and extends it toward the distribution of neurofibrillary tangles which had not been analyzed systematically before. A preferential involvement of sulcal fundi with both tau pathology and Aß pathology has similarly been observed in chronic traumatic encephalopathy (CTE) where it may result from stress concentration at the sulcal depth following trauma .…”
Section: Discussionsupporting
confidence: 91%
“…Both Aß plaques and neurofibrillary tangles were found concentrated in sulcal fundi compared with gyral crowns. This confirms previous observations on the distribution of plaques made by several groups including our own and extends it toward the distribution of neurofibrillary tangles which had not been analyzed systematically before. A preferential involvement of sulcal fundi with both tau pathology and Aß pathology has similarly been observed in chronic traumatic encephalopathy (CTE) where it may result from stress concentration at the sulcal depth following trauma .…”
Section: Discussionsupporting
confidence: 91%
“…Third, the pattern of Ap deposits may be related to another feature of the cortex. Hence, some of the larger clusters may be associated with the tendency for Ap deposit densities to be greater in the superficial corti cal laminae in sulci than gvri [35], In addition, neurofi brillary tangles [33] and arterioles [36] show evidence of a repeating pattern along the cortex. However.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that this area is affected by schizophrenia and Alzheimer's disease (AD) 24–30 . For example, in schizophrenia subjects, a reduction of gray matter in this region has been found 31 .…”
Section: Introductionmentioning
confidence: 99%